Characteristics and postoperative dynamic changes in circulating CD4+ helper T lymphocytes in patients with breast cancer - Lu, Yan; Zhang, Qiaohong; Wang, Jiang; Zhang, Longyi (Frontiers in Oncology, 2023)
Introduction Circulating CD4+ helper T cell (Th) subsets provide potentially important information on disease progression in several cancers. In this study, we explored the characteristics and postoperative dynamic changes in circulating CD4+Th subsets in patients with breast cancer. Methods Circulating CD4+Th subsets, including CD4+ naive T cells (Tn), CD4+ central memory T cells (Tcm), CD4+ effector memory T cells (Tem), CD4+CD57+T, and CD4+PD-1+T, were detected with multiparameter flow cytometry. T-test and Wilcoxon rank-sum test were used to compare differences between groups for normally and non-normally distributed continuous variables, respectively. Postoperative dynamic changes in CD4+Th subsets were assessed using the paired-sample rank-sum test. Results Seventy-five patients with invasive breast cancer and fifty-three patients with benign breast tumors were enrolled. Compared with that in patients with benign tumors, the proportion of CD4+Tn in patients with breast cancer patients decreased, whereas the proportion and absolute number of CD4+CD57+T and CD4+PD-1+T increased. Moreover, the proportion of CD4+PD-1+T was correlated with the clinicopathology of breast cancer. After tumor resection, the proportion and absolute number of CD4+Tcm significantly decreased, while those of CD4+Tem significantly increased, compared with preoperative values. Tumor resection caused significant changes in the proportion and absolute number of CD4+CD57+T and CD4+PD-1+ T, both of which showed significant decreases. Discussion We found significant changes in circulating CD4+Th subsets in patients with breast cancer. Additionally, complete tumor resection can benefit the patient as it balances the patient’s immunosuppression and immune stress and improves the immune exhaustion and immunosenescence states.